Cyclic motion control for programmable bevel-tip needles 3D steering: a simulation study - Matheson,E; Watts,T; Secoli,R; Rodriguez,y Baena F (IEEE, 2019)
Flexible, steerable, soft needles are desirable inMinimally Invasive Surgery to achieve complex trajectorieswhile maintaining the benefits of percutaneous interventioncompared to open surgery. One such needle is the multi-segmentProgrammable Bevel-tip Needle (PBN), which is inspired by themechanical design of the ovipositor of certain wasps. PBNscan steer in 3D whilst minimizing the force applied to thesurrounding substrate, due to the cyclic motion of the segments.Taking inspiration also from the control strategy of the wasp toperform insertions and lay their eggs, this paper presents thedesign of a cyclic controller that can steer a PBN to produce adesired trajectory in 3D. The performance of the controller isdemonstrated in simulation in comparison to that of a directcontroller without cyclic motion. It is shown that, while thesame steering curvatures can be attained by both controllers,the time taken to achieve the configuration is longer for thecyclic controller, leading to issues of potential under-steeringand longer insertion times.